The Effect of Shuttle Run and Zig-Zag Run Exercises on Dribbling Agility in Football School Erla U-12 Students - Rifqi Junda Adiba Putra; Tommy Soenyoto (Journal of Physical Education Health and Sport, 2026)
Dribbling skills are one of the important basic techniques in football that are influenced by the physical condition of the player, especially agility. Based on preliminary observations, players' dribbling skills still need to be improved, especially in terms of dribbling speed and the ability to change direction when passing opponents. This study aims to determine the effect of shuttle run and zig-zag run exercises on increasing ball dribbling agility in Football School ERLA U-12 players in Larangankulon Village. This study uses an experimental method with a pretest-posttest design. The research subjects amounted to 20 Football School  ERLA U-12 players who were divided into two groups, namely the shuttle run training group and the zig-zag run training group. The training program is carried out for 16 meetings with a frequency of three times a week. Data collection was carried out using a dribbling dexterity test, while data analysis used a Kolmogorov-Smirnov normality test and a pair sample t-test. The results showed that the two training methods had a significant influence on increasing the dribbling agility of players with a significance value of 0.000 (p < 0.05). The average increase in the shuttle running group was 0.639 seconds, while in the zig-zag running group it was 0.634 seconds. The results of the effect size analysis showed that both methods had a very large influence, but the zig-zag run exercise showed slightly higher effectiveness. Based on the results of the study, it can be concluded that shuttle run and zig-zag run exercises are effective in improving the dribbling agility of early age soccer players, with zig-zag run training as a more effective method.